In situ evaluation of the food input in the different zones of a cave: case study and methodological recommendations - Dodonov, Pavel; Freitas, Juliana Ribeirão de; Tezori, Rogerio Franco Flores; Bichuette, Maria Elina (Revista da Biologia, 2018)
Due to the absence of light, cave environments are devoid of photosynthesizing organisms, and depend on the input of food from above ground. We compared the quantity of food available in the different zones of two caves in Serra da Canastra, MG. The amount of plant debris was highest in the entrance zone, intermediate in the twilight zone, and minimal in the dark zone. Guano was practically absent from the entrance zone, but did not present any clear pattern between the twilight and the dark zones. Therefore, plant debris seem to be more important in the entrance zone, and guano in deeper zones. We conclude with some methodological recommendations related to the quantification of food input and to statistical inference.